(untitled) (International Journal of Biomedical Research, 2021)
Introduction: Manual BP measurement is associated with white-coat anxiety which may lead to overestimation of BP. Use of ABP device may alleviate the problem and allow emergency physicians and nurses to focus on other resuscitative procedures. ABP also alleviates inter-operator variability. Hence this study was conducted to compare the difference between the blood pressure readings measured by automated method and manual method and to compare the measured blood pressure readings and correlate them with respect to gender and mid arm circumference. Materials and Methods: Conducted in a tertiary care hospital, involved 684 patients. A trained Emergency physician operated the Automated device. The blood pressure was taken in the left arm. Average of these readings was taken as the BP. Bland-Altman plots were used to assess the limits of agreement. The data was analyzed using SPSS version 21. Results: 89 patients were detected hypotensive by MBP while ABP could detect hypotension in only 71.9% (64) of these patients. 75 (100%) patients diagnosed as hypertensive by the MBP were detected as hypertensive by ABP. 38 patients were hypotensive on MBP, ABP detected 84.2 % (32) of the patients. Bland and Altman analysis showed that the limits of agreement are 21.19 to -5.89 for SBP and 19.78 to -4.55 for DBP. Our device obtained a BHS grading of C for both SBP and DBP. As per the AAMI criteria, the standard deviation between ASBP and MSBP was 6.91 with a mean of 7.65. The standard deviation between ADBP and MDBP was 6.21 with a mean of 7.15. Conclusion: We conclude that the ABP can be used with some degree of confidence to assess the blood pressure of walk in-patients with normotension and hypertension but care should be taken when taking BP readings for patients with hypotension and prehypertension.